Penterjemahan ulasan berita Bahasa Melayu ke Bahasa Tamil dalam siaran radio RTM / Selva Kumaran Subrayan - Selva Kumaran, Subrayan (2017)
Translations are very useful in our lives due to the rapid development of world in terms of science, technology, information technology and education. The result of the progress that has been cherished today is the result of the communication happening among people. This communication occurs in a variety of languages spoken by humans. The development of science is a succes if people could understand the communication among them. Therefore, this study was conducted to explore the effectiveness of the translation from the source text of Malay language into the target text of Tamil language. This sudy utilises qualitative method (Creswell, 2002). Data were analyzed and explained descriptively using the guidelines provided in Translation Theory of Eugene A. Nida (1969). Six (6) important aspects of Eugene A. Nida’s Theory of Translation has been used to analyse the text translation in relation to the elements of language (words, phrases, and sentences) and style which makes it difficult for the process of translation to be executed. While the overall quality of the study text is evaluated based on the Holistic Holistic Translation Evaluation Criteria (Adapted and modified from Sanjun Sun (2012: 118). The study has employed five (5) original Malay and five (5) Tamil translation texts. All the original texts and comments of English and Tamil translation were reviewed and broadcasted on RTM radio network within the period of February to March 2013. The findings show that all of the translated texts has adopted formal and dynamic methods for translation. The use of non-similarity equation is less used in the translation of the analysed text. This is due to the lack of cultural element in the analysed text. The findings further reveal that generally, translators had faced difficulties in translating the the whole assigned texts. In addition, the translator also faced difficulties in prose and verse. This is due to the time constraints of the preparation for the broadcasting news. This study concludes that most of the texts can be translated accurately. The total of eight (8) texts meet the criteria of a good level of translation with minimal inaccuracies. The translations describe all of the original passage with only a few lexical errors. While another text meets the criteria of a quite good level of translation with some inaccuracies. Nonetheless, the meaning of single words, phrases, sentences and ideas is rather wrong. In summary, it is impposible for the translation to be done arbitrarily and according to the translators involved in this study, a translation has to go through a number of methods. The use of an appropriate translation method would enhance the accuracy and the quality of the text.